Study of the Best Methodology for Measuring Surface pH of Linen Canvas. (18th August 2021) - Rota, Erica; Bozzi, Claudio; Cremonesi, Paolo; Lucchini, Anna
ABSTRACT: In the preservation of cultural heritage, the measurement of pH has implications both as a parameter for assessing the state of conservation and as a reference for the preparation and use of aqueous treatment solutions. Few studies in the relevant literature, however, deal with evaluating the reliability of measurements. The purpose of this study was to identify the best method and the confidence limits for measurements of surface pH on linen canvas. The results obtained with the two main methods currently used, water drop and rigid gel, were evaluated and compared with warm extraction. Agarose at different concentrations was used for preparing rigid gels, and the influence of the volume of the gel was also evaluated in the latter measurements. Five canvas samples with different degree of acidity were tested: highly acidic, acidic, weakly acidic, a new linen canvas, and the lining canvas recovered from a painting dating around the middle of nineteenth century. The theoretical surface pH values (pHst ), derived from the measurements obtained by the aqueous extraction method, were used as standards against which to assess the reliability of the measurements.